2017
DOI: 10.1055/s-0037-1615275
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal Cyst and Malignancy: A Plea for Lifelong Follow-Up

Abstract: Previous research has confirmed that patients with choledochal cyst have an elevated risk of cholangiocarcinoma and gallbladder carcinoma. Current data suggest a risk of malignancy of 6 to 30% in adults with choledochal cyst. Malignancy has also occasionally been identified in children and adolescents. Multiple factors, including the age of the patient, cyst type, histological findings, and localization, have an impact on the prognosis. Information on long-term outcomes after cyst excision is limited. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…26 The global incidence reported in the word medical literature for cholangiocarcinoma is 0.95 per 100,000, being more frequent in patients with CC. 21,22 The risk of malignancy reported for these patients is 0.7% to 28%, this risk increases over time. 2,5,6,8,23 Sastry et al, in one of their studies with a population of 7,880 patients (1,914 under 18 years of age and 3,866 adults), from which 4.59% had histopathological studies revealing malignancy, 70.4% of these patients had cholangiocarcinoma, 23.5% gallbladder carcinoma, and 6.1% other malignancies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26 The global incidence reported in the word medical literature for cholangiocarcinoma is 0.95 per 100,000, being more frequent in patients with CC. 21,22 The risk of malignancy reported for these patients is 0.7% to 28%, this risk increases over time. 2,5,6,8,23 Sastry et al, in one of their studies with a population of 7,880 patients (1,914 under 18 years of age and 3,866 adults), from which 4.59% had histopathological studies revealing malignancy, 70.4% of these patients had cholangiocarcinoma, 23.5% gallbladder carcinoma, and 6.1% other malignancies.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of cholangiocarcinoma in type I CC is 68%; and in type IV CC it is of 21%. 21 The risk of malignancy is high, and it is associated with a global survival of 6 to 21 years. Incidence of malignancy referred by Amid et al, in type IV CC was of 9.2%, type I 7.6%, type II 4.3%, type III 4%, and type V 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, remnant choledochal cyst has been shown to increase the risk of malignancy. The mechanism of cancer development remains unclear, which may relate to inflammation, cell regeneration and DNA breaks caused by K-ras and p53 mutations [ 9 ]. Malignant cyst occurred mostly in type I and type IVa patients, followed by type V [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cancer development remains unclear, which may relate to inflammation, cell regeneration and DNA breaks caused by K-ras and p53 mutations [ 9 ]. Malignant cyst occurred mostly in type I and type IVa patients, followed by type V [ 9 , 10 ]. Both complications can affect patients’ quality of life as well as survival [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCM can be classified anatomically according to the Todani classification [1] or its derivatives [2], based on morphological appearance and dilatation of the extrahepatic and/or intrahepatic bile ducts. CCM can also be considered a premalignant condition and one systematic review suggested that about 10% of all patients may develop a carcinoma of the biliary tract at some point in life, and usually at a younger age than the normal age of onset of bile duct cancer [3,4]. The long-accepted treatment therefore consists of excision of the entire extrahepatic biliary tree, followed by reconstruction with a Roux-en-Y hepaticojejunostomy.…”
Section: Introductionmentioning
confidence: 99%